Achieving net zero neighborhoods: a case study review of circular economy initiatives for South Wales - Edwards, Jacob; Xia, Hanbing; Li, Qian Jan; Wells, Peter; Milisavljevic-Syed, Jelena; Gallotta, Alberto; Salonitis, Konstantinos (Elsevier, 2024)
Adopting net zero neighborhoods (NZN) combined with circular economy are increasingly recognized as an essential strategy for construction companies, allowing their transition towards sustainability and contributing to climate change mitigation. Transforming existing neighborhoods into NZN is necessary to achieve energy self-sufficiency and net zero by 2050. The success of NZN hinges on government initiatives. However, existing studies appear to lack a comprehensive exploration of the transformation initiatives within NZN, spanning aspects like raw materials, construction practices, transportation, and waste management, particularly in terms of technological advancements. To address the gap, this research introduces a conceptual framework that integrates the multiple case studies design method with an urban transformative capacity model. This innovative framework is the first application of a multi-level urban transformative capacity model in transforming existing neighborhoods into NZN within a specific region. This research specifically utilizes South Wales in the UK as a case study. It identified four key initiatives in technology, construction, transportation, and waste management. These initiatives offer significant benefits, including fostering a more sustainable and environmentally friendly construction industry through enhanced traceability and efficiency, and simultaneously promoting social sustainability by improving community engagement, providing social benefits through sharing economy initiatives, and creating new green job opportunities.
Keywords: Net zero neighborhoods; Circular economy; Urban transformative capacity model; Material passport; Multiple case studies design